2022
DOI: 10.1155/2022/9650650
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Volatile Oil of Rhodiola tangutica against Hypoxia‐Induced Pulmonary Hypertension in Rats Based on RAS Pathway

Abstract: Ethnopharmacological Relevance. Volatile oil is an important bioactive ingredient of Rhodiola tangutica (Maxim.) S.H. Fu, namely, R. tangutica in short. Previous studies have focused on its chemical composition. In our previous research, we found that the bioactive fraction of Rhodiola tangutica could significantly alleviate hypoxia-induced pulmonary hypertension (HPH) in rats. However, it remains unknown whether the volatile oil of Rhodiola tangutica (VORA) could alleviate HPH in rats. Aim of the Study. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The results of the present study also found that Rhodiola L. also inhibits the expression of several hypoxia-induced proteins, such as proliferating cell nuclear antigen (PCNA), cyclin-dependent kinase 4 (CDK4), and cyclin D1 in pulmonary tissue. Rhodiola L. also inhibited the proliferation of rat pulmonary artery smooth muscle cells ( Nan et al, 2022 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…The results of the present study also found that Rhodiola L. also inhibits the expression of several hypoxia-induced proteins, such as proliferating cell nuclear antigen (PCNA), cyclin-dependent kinase 4 (CDK4), and cyclin D1 in pulmonary tissue. Rhodiola L. also inhibited the proliferation of rat pulmonary artery smooth muscle cells ( Nan et al, 2022 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%